SUSTAINABLE DEVELOPMENT IN THE ASPECT OF AUDITING IN CONDITION OF TRANSFORMATION OF SOCIAL INSURANCE SYSTEM - Abdurahmonova, Muqadamkhon Zokirkhonovna (Journal of Environmental Science and Sustainable Development, 2020)
In the modern condition of economy transformation, in the result of reformation of social insurance system appeared different problems. In the result of previous research about the transformation of social insurance system we defined some disadvantages of this sphere expressed in candidate dissertation on theme “Features of development and modernisation of social security system in the national economy of Tajikistan”. The problems regarding to amount of social insurance influenced to the research in the aspect of auditing. So, just by controlling and revision procedures determines economic based decisions for decreasing problems. Methods. In the process of our research, we used several methods of research work, such as, observation, interviews, comparison analyses and accounting calculations by different important primary materials of SASIP (State Agency of Social Insurance and Pension) of Republic of Tajikistan. Results and discussion. In order to the offered theory, used author’s formula (AAR = Ri * Rci * Rnf) and conceptions of auditing influences to the quality of revision process and by solution defined the real condition of the main indicators of social insurance system. The result of this solution improves the process of audit procedures for correctly making decisions. Conclusion. In the modern of sustainable development of economy each sphere must follow to the time requirements. That is why auditors and accountants of any type of companies, just of social insurance system have to work by national confirmed regulations of the country and in the case of appearing any problem organize discussion clubs for solution them.